2003
DOI: 10.1046/j.1492-7535.2003.01221.x
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Related Problems in Hemodialysis Patients

Abstract: Polypharmacy is common in hemodialysis patients. The objective of this study is to identify drug‐related problems (DRPs) in hemodialysis patients, intervene, and resolve them. All patients undergoing dialysis at a hemodialysis center were enrolled into the study. Patients who had been hospitalized during the study period were excluded. DRPs were identified after thorough review of the patients’ medication and clinical records. DRPs were classified into 8 categories and any DRP that did not fit into the 8 categ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Nine additional studies were identified from other sources (manual search and contribution by experts) [29,34,[42][43][44][45][46][47][48].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nine additional studies were identified from other sources (manual search and contribution by experts) [29,34,[42][43][44][45][46][47][48].…”
Section: Resultsmentioning
confidence: 99%
“…After the elimination of duplicates, application of the inclusion and exclusion criteria, consultation of the bibliographies of the selected articles, and consultation with experts (Figure 1), 16 documents with full text available were selected and retrieved [20,29,34,[42][43][44][45][46][47][48][49][50][51][52][53][54]. One of them was a doctoral thesis [34] and was related to another selected study [29].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with end-stage renal disease (ESRD) are at risk of developing drug-related problems (DRPs) due to polypharmacy, multiple co-morbidities and frequent medication changes 1 . Pharmacists are in a unique position in a multidisciplinary healthcare team to identify and solve DRPs by conducting medication reconciliation and educating patients 2 .…”
Section: Introductionmentioning
confidence: 99%